(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
In this article, the model of problem-based learning in the learning process is designed for students’ thinking and consists in creating a problem situation in the minds of children with the formulation of tasks in learning; finding ways to solve the task, expressing hypotheses; applying the chosen method, a hypothetical task to perform; consolidating knowledge by making a conclusion on the completed task, applying the conclusion in practice